The Significance of Orthopedic Journals in Advancing the Orthopedic Society - Joshi, Amit; Regmi, Subhash (Nepal Orthopaedic Association Journal, 2023)
In orthopedic surgery, publishing research findings is of utmost importance, regardless of the practitioners’ geographical location or economic status. While the significance of research publication is widely recognized in developed countries, its value for orthopedic surgeons in developing countries is equally vital. Orthopedic journals play a crucial role in the progression of the orthopedic society by providing a platform for disseminating research, sharing clinical experiences, and promoting evidence-based practice. Understanding the value of the platform, Nepal Orthopedic Association established its journal way back in 2010.